STRATEGIES OF LIBRARY MATERIALS DIGITIZATION IN AN ACADEMIC LIBRARY: A STUDY - Chatterjee, Sutapa; Dey, Bangasree (International Journal of Research -GRANTHAALAYAH, 2023)
This present study focused on different issues related to digitization of library collection of Presidency University, Kolkata. The university being more than 200 years old, houses a number of valuable hand written documents as well as thousands of old and rare books in different language (many of them printed in seventeenth century and eighteenth century). Initiatives have been taken few year back to preserve these documents. About fifty thousand pages of handwritten documents were already been digitized by the library and about ten thousand ‘old and rare’ books are under process. This study talks about the step by step progression of the digitization method followed; analyzed how different challenges are tackled during the process and also the benefits library users are getting from this digitization endeavor of the University library. Finally few suggestions are provided to overcome the challenges for any such future endeavors.